Case series investigating the differences between stimulation of rostral zona incerta region in isolation or in conjunction with the subthalamic nucleus on acute clinical effects for Parkinson’s disease - Lisa Hirt; Kimberly A. Thies; Steven Ojemann; Aviva Abosch; Marielle L. Darwin; John A. Thompson; Drew S. Kern (Interdisciplinary Neurosurgery, 2022)
Background: Subthalamic nucleus (STN) deep brain stimulation (DBS) is a highly effective therapy for movement disorders including Parkinson’s disease (PD). One focus of research has been to explore whether stimulation of the rostral zona incerta (rZI) region contributes to the efficacy observed in STN DBS therapy. Objective: In this study, we conducted a case series to evaluate the clinical efficacy and adverse effects of stimulation to the rZI region in isolation and in conjunction with STN stimulation. Methods: Volunteers with PD (N = 5), treated with STN DBS, and determined to have a dorsal contact within the region of rZI were recruited to participate. Following evaluation of tolerability, each volunteer underwent routine motor assessments during three stimulation parameter conditions: STN, rZI, and co-stimulation STN + rZI. Both participant and clinical examiner were blinded to the condition. Efficacy was measured with the Movement Disorders Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and the Unified Dyskinesia Rating Scale (UDysRS). Volumes of tissue activation for all conditions were assessed for STN and rZI coverage. Results: No significant differences between measures of MDS-UPDRS and UDysRS were observed for the three stimulation settings. Although not statistically significant, results showed that 2 participants preferred STN + rZI co– stimulation, 2 participants preferred STN stimulation, and 1 participant preferred rZI stimulation and 4/5 participant preferences were consistent with clinician preference. Conclusions: Findings from this case series support further investigation into co-stimulation of the rZI region and STN for PD motor symptoms.